From career awareness to career adaptation: the serial mediating role of career transition - Söner, Osman (Frontiers in Developmental Psychology, 2026)
IntroductionCareer awareness plays a critical role in shaping individuals' career paths by enabling them to recognize their skills, interests, and career goals. However, career awareness alone may not be sufficient to ensure career adaptability. It is suggested that this relationship operates through career transition factors, including situational conditions, self-related factors, and social support. Accordingly, this study aimed to examine the mediating role of career transition factors in the relationship between career awareness and career adaptability among high school students.MethodsThe study employed a correlational survey design. Data were collected from 828 high school students attending 10 different schools in Istanbul, Türkiye. Three validated measurement tools were used: the Career Awareness Scale, the Career Transition to Higher Education Scale, and the Career Adaptability Scale. Structural Equation Modeling (SEM) was conducted to test the direct and indirect relationships among variables using IBM SPSS Statistics 29.0 and AMOS 29.0.ResultsThe results indicated that career awareness significantly predicted career adaptability. Moreover, career transition factors-namely situation, self, and social support-partially mediated this relationship. Among these factors, situational conditions and social support demonstrated a stronger mediating effect compared to self-related factors.DiscussionThe findings suggest that students with higher levels of career awareness are more likely to adapt successfully to career-related challenges and transitions, particularly when situational barriers are effectively addressed and adequate social support is available. This study contributes to the career development literature by emphasizing the crucial role of career transition factors in enhancing career adaptability. The results were discussed in relation to existing literature, and practical recommendations were proposed for career guidance and counseling practices.